Sources of Perceived Stress and Coping Strategies among Ghanaian University Lecturers - Lawer Theresa Dede; Adom-Mensah Benedicta Ama; Akoto Justina Sarpong; Ocansey Frederick (Acta Educationis Generalis)
Introduction: The study sought to investigate sources of perceived stress among lecturers of a Ghanaian university and coping strategies they use to mitigate and cope with perceived stress.